2009
DOI: 10.1111/j.1600-0463.2008.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpes virus 8‐unrelated primary effusion lymphoma‐like lymphoma: report of a rare case and review of the literature

Abstract: A rare case of human herpes virus 8-unrelated primary effusion lymphoma-like lymphoma: a report and review of the literature. APMIS 2009; 117:222-29. Primary effusion lymphoma (PEL) is a very rare type of lymphoma usually confined to the body cavities predominantly in immunosuppressed patients infected with human herpes virus 8 (HHV-8). The new term for HHV-8 independent PEL is HHV8-unrelated PEL-like lymphoma. We describe an 89-year-old human immunodeficiency virus (HIV)-negative male patient with HHV8-unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 32 publications
0
58
1
1
Order By: Relevance
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of our cases are in excellent agreement with these characteristics. Kobayashi et al [2] found no association between HHV-8-negative effusion lymphoma and hepatitis B virus (HBV)/hepatitis C virus (HCV) infection, although other authors argued that a substantial number of HHV-8-negative cases were HCV positive [3,4,9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been reported that HHV-8-negative PEL highly expresses B-cell markers, called PEL-like lymphoma [4]. It has also been reported that the malignant cells of HHV-8-unrelated HIV-negative PEL-like lymphoma patients disappear spontaneously without chemotherapy after serous effusion aspiration or drainage [3,[5][6][7][8]. We report two cases of HHV-8-unrelated HIV-negative PEL-like lymphoma in whom no malignant cells were present after effusion drainage alone.…”
Section: Introductionmentioning
confidence: 95%
“…The malignant cells are usually negative for B-cell markers, such as CD19, CD20, and CD79a, but are positive for activation and plasma cell-related markers, such as CD30, CD38, and CD138. The median survival of patients with PEL is \6 months [2,3]. On the other hand, it has been reported that HHV-8-negative PEL highly expresses B-cell markers, called PEL-like lymphoma [4].…”
Section: Introductionmentioning
confidence: 98%